Improved Piracy Site Detection Technique using Search Engine - Kim, Eui Jin; Kim, Deuk Hun; Kwak, Jin (KSII Transactions on Internet and Information Systems, 2022)
With the increase in copyright content exports to overseas markets due to the recent globalization of the Korean culture, the added value of the Korean digital content market is increasing at a significant rate. As such, as the size of the copyright market increases, different piracy sites have emerged that generate profits by illegally distributing works without the permission of the copyright holders, resulting in direct and indirect damage to these copyright holders. The existing copyright detection methods used in public institutions for solving this problem are limited, while the piracy sites are ever-changing. Methods are being continuously developed to achieve better detection results. To this end, it is possible to detect the latest infringement site domain by detecting the infringement site domain that is constantly changed through the search engine. This paper proposes an improved piracy site detection method using a search engine to prevent the damage caused by piracy sites.
Keywords: Added values; Copyright detection; Copyright holders; Copyright infringement; Detection methods; Digital-content market; Globalisation; Overseas markets; Piracy site; Site detection; Copyright Detection; Copyright Infringement; Piracy Site; Search Engine